Social capital and realm of the intellect - Fine, Ben (2001)
The wide range of application and celebration of social capital is acknowledged and, yet the question of what is social capital remains unsatisfactorily answered. Despite its popularity, social capital has created an undercurrent of opposition from progressive scholars with intellectual integrity. As this article argues, they have not been more numerous and outspoken, precisely because it is very hard to generate serious debate and disagreement. Individual advancement aside - an important factor in the rise of social capital - all it reveals is much by way of intellectual bankruptcy and a failure to recognise how social capital's ready accommodation of opposition represents a highly successful form of a legitimising repressive tolerance. - Reproduced
Keywords: Infrastructure development; Social capital